UR_GERICHTE 2014_OG V 14 19. vom 13. Juni 2014 - UR Obergericht (2014)
Kindesschutz. Art. 6 Ziff. 1 EMRK. Art. 29 Abs. 2 BV. Art. 276 Abs. 1, Art. 307 Abs. 1, Art. 310 Abs. 1, Art. 314 Abs. 1 i.V.m. Art. 446 Abs. 1 und Abs. 2, Art. 314a Abs. 1, Art. 314abis, Art. 447 Abs. 1, Art. 449a und Art. 450d Abs. 1 ZGB. Art. 36 Abs. 3 VRPV.